Construção de célula eletroquímica para observação de amostras in situ em estereomicroscópio - Alencar, Mônica Alessandra Silva [UNESP]; Benedetti, Assis Vicente [UNESP]; Fugivara, Cecilio Sadao [UNESP]; Messaddeq, Younes [UNESP] (Sociedade Brasileira de Química, 2010)
The electrochemical study of glass like tungsten oxide derivatives requires the construction of special electrodes due to the fact that these glasses are not conductive. Electrodes modified with WO3 change their color when submitted to some potential perturbation. The color change of the electrochromic materials was observed in situ by coupling an electrochemical cell to a stereomicroscope. The constructed cell is versatile and may represent a great contribution to the electrochemical studies of materials, especially in the systems where it is interest to observe the working electrode surface during the electrochemical experiment.
Construction of an electrochemical cell to visualize samples in situ in stereomicroscope
Keywords: electrochemical cell; stereomicroscope; electrochromism